Nomenclatural and bibliographic corrections to the Catalog of Nabidae (Hemiptera: Heteroptera) for the Neotropical Region - Coscarón, Maria Del Carmen; Volpi, Lorena N. (Zootaxa, 2013)
The recent catalog of Neotropical Nabidae is corrected and updated. Synonymies, species, and references that were overlooked are now included. 11 genera and 83 species are presently known from this region.